Challenges in Providing Trainings for English Teachers of Elementary Schools - Nury Supriyanti (Intelektual Pustaka Media Utama, 2012)
Primary English provision in Indonesia has started in 1994 in which English has the position as the local content subject in the elementary schools. English has then been part of the Indonesian elementary schoolchildren’s daily routines in many different ways. In the major cities, which are geographically then educationally more privileged, the children might enjoy their English lessons because they have the qualified teachers who know English and how to teach it to young learners, they have appropriate and interesting materials as well as appropriate techniques to learn by. The case is quite different for the children of the less privileged areas where access to qualified teachers, appropriate materials and fun learning is almost impossible. These children have to be content with teachers with no English or child teaching background who are hired because only them who are available. The paper describes the struggle of the English Education department of the Yogyakarta State University in the development of the EFC courses in order to contribute to the provision of English to elementary schools in Indonesia.